A pilot play-based intervention to improve the social play interactions of children with autism spectrum disorder and their typically developing playmates - Henning, B.; Cordier, Reinie; Wilkes-Gillan, S.; Falkmer, Torbjorn (Wiley-Blackwell Publishing Asia, 2016)
Background/aim: Occupational therapists play a key role in addressing the social difficulties of children with ASD. However, interventions are often time intensive, without outcomes generalising beyond the clinic setting. To examine the feasibility and preliminary effectiveness of an intervention to address the social play skills of children with ASD. Methods: Participants in this multiple case study design were five children with autism spectrum disorder (ASD), five typically developing playmates and five parents of children with ASD. Two therapists and parents delivered the intervention involving clinic play sessions and home modules. Parents' treatment adherence was recorded. The Test of Playfulness was scored by a blinded rater to examine child outcomes following the intervention. Line graphs were used to examine case data. Percentage of non-overlapping data (PND) was used to calculate the single-case effect size for each child. Results: Parents completed 92.2% of the intervention. Children's case data showed an upwards trend from pre- to post-intervention in four of the five pairs (child with ASD and playmate). However, there was a decrease in scores from post-intervention to the two-month home follow-up for all but one pair. PND indicated the intervention was effective for two children with ASD and three of their playmates, had a questionable effect on three children with ASD and no observable effect on two playmates. Conclusion: The intervention demonstrated preliminary feasibility and effectiveness for improving the social play skills of some children with ASD. Careful consideration is needed to identify which children with ASD and which playmates would be best suited for this intervention approach.